Insertion Algorithms with Justification for Solving the Resource-Constrained Project Scheduling - Klimek, Marcin; Łebkowski, Piotr (Decision Making in Manufacturing and Services, 2017)
The paper presents the resource-constrained project scheduling problem with the makespan minimisation criterion. To solve the problem, the authors propose insertion algorithms which generate schedules with use of forward serial and parallel decoding procedures. Schedules are improved with the use of the double justification by extremes technique (first right and then left justification). The efficiency of the procedures proposed is tested on standard test problems from the PSPLIB library.